2022
DOI: 10.3390/molecules27186057
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Anti-Cancer and Anti-Inflammatory Properties of 25 High-THC Cannabis Extracts

Abstract: Cannabis sativa is one of the oldest cultivated plants. Many of the medicinal properties of cannabis are known, although very few cannabis-based formulations became prescribed drugs. Previous research demonstrated that cannabis varieties are very different in their medicinal properties, likely due to the entourage effect—the synergistic or antagonistic effect of various cannabinoids and terpenes. In this work, we analyzed 25 cannabis extracts containing high levels of delta-9-tetrahydrocannabinol (THC). We use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…According to this study, THC and CBD standards inhibited the cytochrome c activity in bovine heart membranes with similar concentration response curves. This discrepancy between the effect observed with pure cannabinoid standards and correlation studies with complex samples has also been reported in Cannabis sativa strains with high THC content, and could be due to other molecules, such as terpinene [ 30 ]. Indeed, it has been shown that the combination of THC and CBD is more effective for multiple sclerosis treatment [ 31 ] and pain relief [ 32 ].…”
Section: Discussionmentioning
confidence: 83%
“…According to this study, THC and CBD standards inhibited the cytochrome c activity in bovine heart membranes with similar concentration response curves. This discrepancy between the effect observed with pure cannabinoid standards and correlation studies with complex samples has also been reported in Cannabis sativa strains with high THC content, and could be due to other molecules, such as terpinene [ 30 ]. Indeed, it has been shown that the combination of THC and CBD is more effective for multiple sclerosis treatment [ 31 ] and pain relief [ 32 ].…”
Section: Discussionmentioning
confidence: 83%
“…In previous studies on breast and lung tumor cell lines, THC was seen to have a dose-dependent, inhibitory cell proliferation effect [ 35 , 36 ] through its actions on the EGFR pathway. However, this dose-dependent effect has not been observed in other studies on tumoral cell lines, which exposed the cells to plant extracts with high THC content; however, the higher inhibition of cell growth was described [ 37 ].…”
Section: Discussionmentioning
confidence: 79%
“…This action of the Cannabis sativa plant extracts used in our study was not only mediated by the cannabinoid receptor’s activity, but also by its effect on the mETC complexes, among others, which promote oxidative stress. Moreover, the use of plant extracts has demonstrated higher antitumoral effects than cannabinoids by themselves [ 37 ]. However, the content of the antioxidants used in these extracts was not considered.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the compounds identified in this study have previously been reported to possess therapeutic effects [13,14,16,32,[40][41][42][51][52][53][54][55]59]. For instance, linalool is neuroprotective [60], antiinflammatory [61], and antidepressant [62]; pinene possesses an anxiolytic effect [63], ameliorates memory impairment [64], and acts as an analgesic [65]; bulnesol has anticancer [66] and antianxiety properties [67]; humulene acts as an anti-bacterial and antitumor [68,69] agent and inhibits gastric lesions in gastritis [70]; myrcene possesses sedative, analgesic, and antipsychotic properties [13]; and limonene has antibacterial, anxiolytic, immunostimulant, and antidepressant effects [14].…”
Section: Identification Of Terpenes and Terpenoids In Six Cannabis St...mentioning
confidence: 92%
“…The number of compounds detected in each terpene and terpenoid region varied in all six cannabis strains. In Pink Kush, Afghani Drifter, Blue Dream, Ultra Sour, and Western Frost, the number of sesquiterpenes (33,32,25,37, and 28, respectively) was highest followed by sesquiterpenoids (28, 19, 17, 34, and 18, respectively), monoterpenoids (12, 11, 11, 28, and 11, respectively), and monoterpenes (5, 5, 10, 16, and 9, respectively). In Reeferman's Rockstar, the number of sesquiterpenoids was 36, which was the highest followed by 33 sesquiterpenes, 14 monoterpenoids, and 6 monoterpenes.…”
Section: Identification Of Terpenes and Terpenoids In Six Cannabis St...mentioning
confidence: 99%